PRICE STABILIZATION AND IPO UNDERPRICING: AN EMPIRICAL STUDY IN THE INDONESIAN STOCK EXCHANGE - Suad Husnan; Mamduh M. Hanafi; Muhammad Munandar (Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
We attempt to investigate IPO underpricing and stabilization activities. We find IPO underpricing of around 25% in the Indonesia market. Return distribution for the first 30-trading days shows a positive skew, the distribution becomes closer to normality as the period lengthens. We then develop and test five algorithms to detect IPO intervention. An important goal of this paper is to develop an algorithm that will be able to detect IPO intervention using public data. We find that the number of closing prices that are equal to the offer prices and the skewness of the IPO return in the first 30-trading days are the ‘best’ stabilization measures. Having found “the best measures”, then we investigate under what conditions IPO intervention is more intensive. We find that underwriters tend to stabilize more on more expensive IPOs.